AGE AND WORK EXPERIENCES TO FATIQUE FEELINGS AND WORK PRODUCTIVITY RELATIONSHIP OF PALM OIL FRUIT BUNCH HARVEST WORKERS - Humaira' Kanajmi; Meizul Zuki; Damres Uker (BPFP Faperta UNIB, 2017)
Purpose of this research was to analyze the correlation between the factor of age with fatigue of worker, the factor of working experience with fatigue of worker, the factor of age and working experience with fatigue of worker, and fatigue of workers with work productivity in palm oil harvesting. Data were collectedby using quisionere. The analytical method used in this research is the analysis of correlation and linear regression.From the results of this study concluded that there was a significant, quite strong (r = 0.469) and in the same direction (positive) correlation between the age worker factor with fatigue of palm oil harvester by linear regression equation ????1 = 2,571 + 0,077 X1, there was a significant, but low (r = -0.344) and not in the same direction (negative) correlation between the factor of working experience with fatigue of palm oil harvester by linear regression equation ????1 = 6,303 - 0,067 X2, there was a significant and very strong correlation (R = 0.922) between factors of age and working experience with fatigue of palm oil harvester by linear regression equation ????1 = 0,742 + 0,178 X1 - 0,195 X2, and there was a significant, but low (r = -0.271) and not in the same direction (negative) correlation between the fatigue of workers with productivity of palm oil harvesting by linear regression equation ????2 = 258,45- 6,979 X. Labor of palm oil harvesting should be managed by factor age of workers and work experience in order to minimize fatigue of workers so that can improve productivity.